2010
DOI: 10.1002/pola.24487
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of 3‐arm and 4‐arm star‐branched polystyrene Ru(II) complexes by the click‐to‐chelate approach

Abstract: Metal template synthesis is a useful methodology to make sophisticated macromolecular architectures because of the variety of metal ion coordination. To use metal template methodology, chelating functionalities should be introduced to macromolecules before complexation. In this article, we demonstrate the click‐to‐chelate approach to install chelating functionality to polystyrene (PS) and complexation with Ru(II) ions to form 3‐arm and 4‐arm star‐branched PS Ru(II) complexes. Azide‐terminated PS (PS‐N3) was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
(10 reference statements)
2
21
0
Order By: Relevance
“…60,133 Study of an analogous complex [Ru(1) 2 ](PF 6 ) 2 confirmed the geometry of the polymer-appended complex. Polymers such as polystyrene, poly(n-butyl acrylate), poly(n-hexyl isocyanate), poly(caprolactone) and poly(styrene oxide) were used in various combinations.…”
Section: Incorporation Into Polymers Macromolecules and Surfacesmentioning
confidence: 71%
See 4 more Smart Citations
“…60,133 Study of an analogous complex [Ru(1) 2 ](PF 6 ) 2 confirmed the geometry of the polymer-appended complex. Polymers such as polystyrene, poly(n-butyl acrylate), poly(n-hexyl isocyanate), poly(caprolactone) and poly(styrene oxide) were used in various combinations.…”
Section: Incorporation Into Polymers Macromolecules and Surfacesmentioning
confidence: 71%
“…59 This research demonstrated that synthesis of the btp based ligand provided easy access to a class of terdentate ligands, possessing a terpy-like coordination environment, but with distinctive differences such as the broad scope of functionalisation available via the CuAAC reaction and size differential between the heterocyclic rings. Hence, btp provides a promising method of introducing terpy-like functionality to macromolecules because of the excellent feasibility of azide substitution and 'click' chemistry, 60 as was also discussed above.…”
Section: The Btp Motifmentioning
confidence: 99%
See 3 more Smart Citations